Design of Web-Based Decision Support System Using AHP and bcrypt Security - Subagio, Moh. Mario; Mumpuni, Retno; Nurlaili, Afina Lina (bit-Tech, 2026)
This study presents the development of a web-based decision-support system to prioritize village administrative services using a structured, data-driven approach. This research addresses a gap in existing systems, which generally lack integration of systematic decision-making methods and robust security mechanisms, leading to inefficiency, low transparency, and subjective decision-making in village administrative processes. To overcome these limitations, the system integrates the Analytical Hierarchy Process (AHP) to evaluate multiple criteria, including submission time, document completeness, urgency level, service type, and request frequency, thereby enabling qualitative assessments to be transformed into measurable, comparable priority values. In addition, the bcrypt algorithm enhances system security by protecting user authentication data through password hashing, thereby mitigating risks such as unauthorized access, brute-force attacks, and rainbow-table attacks. The system is developed as a web-based application to ensure accessibility, scalability, and centralized data management. Evaluation results indicate that the system produces consistent and reliable priority rankings, as evidenced by a Consistency Ratio (CR) within the acceptable threshold, and demonstrates improved decision accuracy and operational efficiency compared to conventional manual approaches. Document completeness is identified as the most influential criterion in determining service priority. Furthermore, the proposed system offers broader applicability beyond village administration, particularly in other public service domains requiring transparent, efficient, and secure decision-making processes. Overall, this study contributes by integrating AHP and bcrypt within a unified system to enhance both decision quality and data security in digital administrative services.